Synthesis of palm oil-derived biocompatible polymeric surfactants for natural rubber latex application / Yvonne Ling Tze Qzian - Yvonne Ling , Tze Qzian (2022)
Surfactant is important for NR latex applications. It serves as latex preservative to preserve latex and promote good NR film formation. However, some surfactants are toxic and skin irritant. Hence, this study aims to develop alternative green, specifically bio-based surfactant from palm oil for natural rubber latex applications. The objectives of this study are to (i) synthesize a series of biocompatible palm oil-derived polymeric surfactants and characterize the physicochemical properties of the surfactants, (ii) evaluate the in vitro cytotoxic and antimicrobial properties of surfactants, (iii) compound surfactants into natural rubber (NR) latex and investigate the rheological properties of the latex, and (iv) study the mechanical properties of NR latex films incorporated with the synthesized palm oil-derived polymeric surfactants. Four palm oil-derived polymeric surfactants, namely palmitic acid anionic surfactant (PAS), stearic acid anionic surfactant (SAS), oleic acid anionic surfactant (OAS) and oleic acid non-ionic surfactant (ONS), were synthesized using polyesterification method. The chemical structures of the surfactants were then confirmed using FT-IR and 1H-NMR. ONS experienced the highest extent of polyesterification, followed by PAS, SAS and OAS. Consistent with the extent of reaction completion, ONS exhibited the highest Mn and Mw values among all four surfactants. One of the highlights of this project is to develop a polymeric surfactant which is biocompatible for NR latex application. It is therefore crucial to evaluate the cytotoxicity of the developed product. All four surfactants, PAS, SAS, OAS, and ONS were subjected to cytotoxicity study using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays. SDS and Tween 80 were included in the study as controls. The cytotoxicity of these four surfactants were evaluated in terms of cell viability against four cell lines, including human keratinocytes (HaCaT), mouse fibroblasts (3T3), mouse hepatocytes (H2.35) and canine kidney cells (MDCK). Comparative cytotoxicity test revealed that the cell viability of these four surfactants were well above 80 %, except for SAS which exhibited low cytotoxicity on fibroblasts after prolonged exposure at high concentration. Antimicrobial test was conducted on OAS and ONS using minimum bactericidal concentration (MBC) assay against bacterial strains methicillin-sensitive S. aureus (MSSA), methicillin-resistant S. aureus (MRSA), K. pneumoniae, and A. baumannii. Subsequent results revealed that OAS is the most effective surfactant in inhibiting the growth of those tested bacteria. The synthesized OAS and ONS were also compounded into NR latex at five various concentrations and subjected into rheological study. From the study, OAS exhibited better outcome with longer linear viscoelastic region (LVR), signifying its potential usage for long term latex stabilization. Mechanical properties of unaged and aged NR films compounded with OAS and ONS in five varies concentrations were also evaluated. Based on the results obtained, it is suggested that NR films incorporated with OAS could form softer films and exhibited anti-aging properties.